Impact of COVID-19 on lifestyle-related behaviours- a cross-sectional audit of responses from nine hundred and ninety-five participants from India. Issue 6 (November 2020) - Chopra, Sakshi; Ranjan, Piyush; Singh, Vishwajeet; Kumar, Suraj; Arora, Mehak; Hasan, Mohamed Shuaib; Kasiraj, Rhytha; Suryansh; Kaur, Divjyot; Vikram, Naval K.; Malhotra, Anita; Kumari, Archana; et al.
Abstract: Background and aims: The impact of measures taken to contain COVID-19 on lifestyle-related behaviour is undefined in Indian population. The current study was undertaken to assess the impact of COVID-19 on lifestyle-related behaviours: eating, physical activity and sleep behaviour. Methods: The study is a cross-sectional web-based survey. A validated questionnaire to assess the changes in lifestyle-related behaviour was administered on adults across India using a Google online survey platform. Results: A total of 995 responses (58.5% male, mean age 33.3 years) were collected. An improvement in healthy meal consumption pattern and a restriction of unhealthy food items was observed, especially in the younger population (age <30 years). A reduction in physical activity coupled with an increase in daily screen time was found especially among men and in upper-socio-economic strata. Quarantine induced stress and anxiety showed an increase by a unit in nearly one-fourth of the participants. Conclusions: COVID-19 marginally improved the eating behaviour, yet one-third of participants gained weight as physical activity declined significantly coupled with an increase in screen and sitting time. Mental health was also adversely affected. A detailed understanding of these factors can help to develop interventions to mitigate the negative lifestyle behaviours that have manifested during COVID-19. Highlights: COVID-19 has affected every aspect of the lifestyle of citizens. Slight improvement was seen in eating behavior, majorly by reduction in intake of high fat, sugar, salt and sugar foods. A significant decline was seen in overall physical activity coupled with increase in sitting and screen time. One third of the sample gained weight during COVID-19.